Exploiting phenotypic plasticity in animal breeding - Kebede, Fasil Getachew; Komen, Hans; Dessie, Tadelle; Hanotte, Olivier H.; Kemp, Stephen J.; Barros, C.P.; Crooijmans, R.; Derks, M.; Alemu, S.W.; Bastiaansen, John W.M. (Wageningen University & Research, 2022)
Livestock populations can have different genetic backgrounds and may vary in their capacity to respond to environmental changes. Our findings suggest that improved chicken breeds differ in growth performance and phenotypic plasticity (yield stability) when they are introduced into new tropical environments. Dual consideration of productivity and phenotypic plasticity gives opportunities to select or recommend genotypes with optimal performance and wider adaptability for smallholder farmers raising livestock in different agroecologies.